Metacognition - Rhodes, Matthew G. (Teaching of psychology, 2019)
Metacognition refers to a set of processes an individual uses in monitoring ongoing cognition so as to effectively control his or her own behavior. In this article, I discuss key frameworks for characterizing metacognition and describe approaches to measuring metacognition. Modern research in metacognition assumes that monitoring of cognition plays a causal role in self-regulation of cognitive processes, making it imperative that monitoring of cognition is accurate. Accordingly, I describe research on metacognitive accuracy and several factors that reliably impact metacognitive accuracy. I conclude by discussing emerging issues and approaches to teaching metacognition.